I have this string of questions, but when I look up depressed cubic, I don't quite understand. I'm not asking for all of these questions to be answered explicitly, but for some explanation on depressed cubics and solving them algebraically. Thanks.

a) Show that the β€œdepressed” cubic equation $π‘Žπ‘₯^3 + 𝑏π‘₯ + 𝑐 = 0$ can be solved geometrically for its real roots on a rectangular Cartesian coordinate system on which the cubic curve $𝑦 = π‘₯^3$ has been carefully drawn, by merely drawing the line $π‘Žπ‘¦ + 𝑏π‘₯ + 𝑐 = 0$. Explain.

b) Solve, by the method of (a), the cubic equation $π‘₯^3 + 6π‘₯ βˆ’ 15 = 0$.

c) Solve the cubic equation $4π‘₯^3 βˆ’ 39π‘₯ + 35 = 0$ geometrically.

d) Show that any complete cubic equation $π‘Žπ‘₯^3 + 𝑏π‘₯^2 + 𝑐π‘₯ + 𝑑 = 0$ can be reduced to the β€œdepressed” form in the variable 𝑧 by the substitution: $π‘₯ = 𝑧 βˆ’ \frac{b}{3a}$.

e) Now solve the cubic equation $π‘₯^3 + 9π‘₯^2 + 20π‘₯ + 12 = 0$ geometrically as described in (a) and (d).


Well, a depressed cubic as you put it; has no quadratic part (no $x^2$ term). The trick here is to realise that when you are trying to find its root, you are solving the equation:

$$ ax^3 + bx + c = 0 $$

You'll see that if you substitute:

$$ y = x^3 $$

you'll just get:

$$ a(x^3) +bx + c= ay+bx+c = 0 $$

So it amounts to solving $ay+bx+c = 0$ simultaneously with $x^3$. You can see this in this desmos demonstration:


ps: this is the basic idea on which the cubic equation is derived ;)

| cite | improve this answer | |

A depressed cubic equation is a cubic with the second degree term missing. (i.e. b=0) Every cubic equation can be transformed into a depressed cubic using the substitution in d).

Do you agree that the curve $y=x^3$ and the line $ay+bx+c=0$ will intersect at the point whose $x$ coordinate satisfies the equation $ax^3+bx+c=0$?

You are not being asked to solve algebraically at this point! This was only the first step in solving algebraically. Then your reduced equation (with a=1) is compared with the identity $$(e+f)^3-3ef(e+f) -(e^3+f^3)=0$$ $$x^3+6x-15=0$$ $x$ will be $e+f$, $-3ef=6$ and $e^3+f^3=15$ The second equation lets you find $f$ in terms of $e$ Then substituting into the third equation gives you a quadratic in $e^3$ which you solve. You should then take the cube root and find $f$ and add them together to get $x$.

| cite | improve this answer | |
  • $\begingroup$ I'm not sure I understand where you're coming from with your e and f notation? $\endgroup$ – K Math Oct 11 '18 at 16:05
  • $\begingroup$ That equation is an identity. It is always true, no matter what letters we use. The deal is we are trying to find x, so we decide to break it into a sum but we don't know what the addends are, Pretending x=e+f and using that identity we can find the $e^3$ and $f^3$ $\endgroup$ – judith Khan Oct 11 '18 at 16:16

Your Answer

By clicking β€œPost Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.